Investigating The Implementation Of Flipped- Differentiated Learning In The Context Of Efl Learners - Kristoforus Gustian; Desy Rusmawaty; Ventje Jany Kalukar (Departement of Mathematics Education, 2023)
This study examines the implementation of flipped-differentiated learning in the context of English as a Foreign Language (EFL) learners. Flipped learning is an instructional approach that reverses the traditional classroom model, where students engage with content outside of class and participate in interactive activities during class time. Differentiated learning, on the other hand, focuses on tailoring instruction to meet individual students' needs and learning styles. This integration of flipped and differentiated learning has the potential to enhance EFL instruction by providing personalized learning experiences and promoting active engagement among students. The objective of this research is to investigate how the two English teachers of a certain Senior High School In Samarinda conduct the integration, the opportunities, and the challenges they discover during the implementation of flipped-differentiated learning in EFL classrooms. The study employs a qualitative case study and the data is collected through open-ended questionnaire and depth interview, analyzed thematically to gain insights into teacher's experiences of this instructional approach. The findings of this study shows the process, the opportunities, and challenges of implementing this integration and hope to inform future research on integration that promote active learning and personalized instruction in language classrooms with the complete data and extent context.